Endoscopic resection is effective for the treatment of bleeding gastric hyperplastic polyps in patients with and without cirrhosis - Nelson, Matthew; Ganger, Daniel; Keswani, Rajesh; Grande, David; Komanduri, Srinadh (Endoscopy International Open, 2016)
Background and study aims: Gastric hyperplastic polyps (GHP) have been identified as a cause of transfusion-dependent iron-deficiency anemia (tIDA) and transfusion-dependent gastrointestinal bleeding and are commonly identified in the setting of cirrhosis. The aim of this study was to assess the effectiveness of endoscopic resection (ER) for the treatment of tIDA or gastrointestinal bleeding due to GHP in patients with and without liver disease.Patients and methods: This was a single-center retrospective review. The primary outcome was clinical success of ER (no transfusion or repeat ER in the following 6 months after first ER). Secondary outcomes included technical success, recurrence of GHP with tIDA or gastrointestinal bleeding, and adverse events (AEs).Results: Sixty-three patients with GHP were included of whom 20 (31 %) had cirrhosis. The majority with cirrhosis presented with gastrointestinal bleeding (n = 13, 65 %, P = 0.52), whereas the majority of non-cirrhotics presented with tIDA (n = 30, 70 %, P = 0.01). Technical success was 100 % with no AEs. The clinical success rate was 94 % (95 % in cirrhotics, 93 % in non-cirrhotics, P = 0.46). The recurrence rate was 32 % (40 % in cirrhotics and 28 % in non-cirrhotics, P = 0.35) with mean time to recurrence of 17.3 ± 13.9 months (P = 0.22). Of those with recurrence, 75 % had no further tIDA or gastrointestinal bleeding after repeat ER (mean follow-up 20 ±11 months). Conclusions: ER is an effective treatment for GHP that causes tIDA or gastrointestinal bleeding. Patients with GHP and cirrhosis tend to present with bleeding rather than anemia and have more frequent recurrence. Symptomatic recurrence of GHP is common and should be recognized early as repeat ER appears to be effective.